1994
DOI: 10.1029/94gl02660
|View full text |Cite
|
Sign up to set email alerts
|

Observations of the 5‐day wave in the mesosphere and lower thermosphere

Abstract: The 5‐day planetary wave has been detected in the winds measured by the High Resolution Doppler Imager (HRDI) on the Upper Atmosphere Research Satellite (UARS) in the mesosphere and lower thermosphere (50–110 km). The appearances of the 5‐day wave are transient, with a lifetime of 10–20 days in the two‐year data set. The structures of selected 5‐day wave events are in generally good agreement with the (1,1) Rossby normal mode for both zonal and meridional components. A climatology of the 5‐day wave is presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
141
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(160 citation statements)
references
References 16 publications
19
141
0
Order By: Relevance
“…The amplitude increase and phase decrease with increasing altitude appear to be continuous from the lower stratosphere to MLT heights. There have been several observations and theoretical studies on planetary scale waves of having periods of between five and eight days in the mesosphere and lower thermosphere (Wu et al 1994;Meyer and Forbes 1997;Kovalam et al 1999;Talaat et al 2001Talaat et al , 2002Lieberman et al 2003;Liu et al 2004). As in the present study, these waves have, in general, been identified as symmetric Rossby waves.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The amplitude increase and phase decrease with increasing altitude appear to be continuous from the lower stratosphere to MLT heights. There have been several observations and theoretical studies on planetary scale waves of having periods of between five and eight days in the mesosphere and lower thermosphere (Wu et al 1994;Meyer and Forbes 1997;Kovalam et al 1999;Talaat et al 2001Talaat et al , 2002Lieberman et al 2003;Liu et al 2004). As in the present study, these waves have, in general, been identified as symmetric Rossby waves.…”
Section: Discussionsupporting
confidence: 65%
“…Different sources have been suggested for the generation of these waves. Wu et al (1994) identified the wave as a Doppler-shifted 5-day wave of normal mode. However, as the wave shows distinct phase variation with height and the change of the 5-day wave period due to Doppler shift would be less than 0.5 days (Geisler and Dickinson 1979), Meyer and Forbes (1997) proposed that the wave could be generated at middle and high latitudes due to baroclinic/barotropic instabilities, which could act as an in situ wave source for the planetary wave.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates the possibility of the persistence of 4-5 cycles to be typical for the 5-day wave oscillations in the upper atmosphere and ionosphere over Central Europe. Wu et al (1994) reported shorter persistence for the 5-day wave events in the mesospheric winds as observed by HRDI/UARS. This might be caused either by different criteria for persistence, or by a difference in latitudes (UARS observations of planetary waves concern predominantly low latitudes).…”
Section: Discussionmentioning
confidence: 69%
“…In the stratosphere, the waves with periods of 4-5 days occur as bursts of several cycles, as deduced from satellite measurements of temperature fields. In the mesosphere, satellite measurements of winds at altitudes of 50-100 km reveal the transient 5-day wave with a lifetime of 10-20 days (Wu et al, 1994). In the mesopause region the tidal winds observed in Central Europe (Collm) in the first half of 1984 were dominated by oscillations with typical periods of 5-6 days, with a typical persistence of 6 cycles for meridional and 4 cycles for zonal component (Laštovička andŠauli, 1999).…”
Section: Introductionmentioning
confidence: 98%
“…Those planetary waves represent "normal mode" or "resonant" oscillations of the atmosphere (e.g., Salby 1984). Global climatology of 2-, 5-, 10-and 16-day waves has been established by satellite measurements, e.g., Gu et al (2013), Moudden and Forbes (2014) for 2-day waves; Wu et al (1994) If the amplitude of the planetary waves is sufficiently large in the dynamo region, they will drive ionospheric currents and affect geomagnetic perturbations on the ground. Even if the planetary waves dissipate before they reach the dynamo region, they can still interact with tides and mean flow in the middle atmosphere, which will affect the upward propagation of tides to the dynamo region, and thus affect the ionospheric dynamo (e.g., Liu et al 2010;Chang et al 2011).…”
Section: Planetary Wave Effectmentioning
confidence: 99%